Catalytic activity of water molecules in gas‐phase glycine dimerization. Issue 20 (12th September 2020) - Gale, Ariel G.; Odbadrakh, Tuguldur T.; Shields, George C.
Abstract: The dimerization of glycine is the simplest oligomerization of amino acids and plays an important role in biology. Although this reaction is thermodynamically unfavorable in the aqueous phase, it has been shown to be spontaneous in the gas phase and proceeds via two different concerted reaction mechanisms known as cis and trans . This may have profound implications in prebiotic chemistry as common atmospheric prenucleation clusters are thought to have participated in gas‐phase reactions in the early Earth's atmosphere. We hypothesize that particular arrangements of water molecules in these clusters could lead to lowering of the reaction barrier of amino acid dimerization and could lead to abiotic catalysis toward polypeptides. We test our hypothesis on a system of the cis transition state of glycine dimerization solvated by one to five water molecules using a combination of a genetic algorithm‐based configurational sampling, density functional theory geometries, and domain‐based local pair natural orbital coupled‐cluster electronic structure. First, we discuss the validity of the model chemistries used to obtain our results. Then, we show that the Gibbs free energy barrier for the concerted cis mechanism can indeed be lowered by the addition of up to five water molecules, depending on the temperature. Abstract : The formation of oligopeptides and polypeptides started before the machinery of biology through natural catalysis of peptide bond formation. The ability of gaseous water molecules to catalyze this reaction is explored using quantum chemistry. The Gibbs free energy barrier for glycine dimerization is lowered by the addition of individual water molecules that stabilize the transition state, thereby catalyzing peptide bond formation.